PENGARUH PELATIHAN, DISIPLIN KERJA, DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV. SAPU DUNIA SEMARANG - Afni Fuanida (Universitas Diponegoro, 2012)
The purpose of this research aims to determine whether the training, work discipline and motivation effect on employee productivity CV. Sapu Dunia Semarang. CV Sapu Dunia is a company which is specification in employee management. The research method effected is Explanatory Research. The sampel research is 100 respondent use the Purposive Sampling, and the data collected with questionnaire. The research result show that the effect of variable training on employee productivity CV. Sapu Dunia Semarang was good. It is shown by 59,8 percent of respondents.Then, the effect of work discipline was good too, it is shown by 57,9 percent of respondents, and 28,9 percent of respondents had thehigh work motivation on CV. Sapu Dunia Semarang. Based on the results of hypothesis testing significantly show that the effect of the training, work discipline and motivation on employee work productivity CV. Sapu Dunia Semarang The effect positive given by the training variable on employee work productivity that the effect evidenced through the test of 12.077 t count bigger than t table 1.985. Then The effect positive given by the work dicipline variable on employee work productivity that the effect evidenced through the test of 11.605 t count bigger than t table 1.985. And The effect positive given by the motivation variable on employee work productivity that the effect evidenced through the test of 6,315. F-test shows that effect of the training, work discipline, and motivation variable have effect on employee work productivity CV. Sapu Dunia Semarang. The score of standardized coefficients beta of the training, work discipline, and motivation variable is 0,406; 0,395; and 0,147. This is show that the training, variable have a bigger effect than the work discipline, and motivation variable